2003
DOI: 10.1001/archpsyc.60.7.720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Selective Serotonin Reuptake Inhibitors During Pregnancy on Serotonergic Symptoms in Newborns and Cord Blood Monoamine and Prolactin Concentrations

Abstract: Infants exposed to SSRIs during late pregnancy are at increased risk for serotonergic central nervous system adverse effects, and the severity of these symptoms is significantly related to cord blood 5-HIAA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
250
4
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(264 citation statements)
references
References 32 publications
6
250
4
4
Order By: Relevance
“…A large fraction of children exposed in utero to SSRIs have been reported to display signs of antidepressant withdrawal in the first week or two of life (Nordeng et al, 2001;Laine et al, 2003;Zeskind and Stephens, 2004;Sanz et al, 2005), indicating that the fetus can be exposed to neurobiologically relevant doses of these drugs. In fact, significant SSRI and metabolite concentrations have been detected in both umbilical cord blood and amniotic fluid in women taking these medications during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A large fraction of children exposed in utero to SSRIs have been reported to display signs of antidepressant withdrawal in the first week or two of life (Nordeng et al, 2001;Laine et al, 2003;Zeskind and Stephens, 2004;Sanz et al, 2005), indicating that the fetus can be exposed to neurobiologically relevant doses of these drugs. In fact, significant SSRI and metabolite concentrations have been detected in both umbilical cord blood and amniotic fluid in women taking these medications during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies [3][4][5][6][7][8][9] have reported relatively consistent findings on the adverse effects of SSRI use during pregnancy, which include neonatal withdrawal syndrome, low birth weight, and preterm birth. Many studies [10][11][12] have indicated no major fetal malformations higher than the baseline population risk of 1% to 3% with use of SSRIs during pregnancy.…”
mentioning
confidence: 99%
“…It and other SSRIs have become increasingly used for the treatment of depression in pregnancy because of their effectiveness and lower incidence of maternal side effects and wider safety margin compared with tricyclic antidepressants and monoamine oxidase inhibitors (4,5). However, there have been several reports that use of these drugs during pregnancy can increase the incidence of adverse pregnancy outcomes, including preterm delivery, fetal growth restriction, and poor neonatal adaptation (5)(6)(7)(8). There is also evidence for postnatal consequences of prenatal SSRI exposure, including reduced weight gain, slight delays in psychomotor development and motor movement control, and our own findings of reduced facial and heart rate responses to painful stimuli (9 -11).…”
mentioning
confidence: 99%
“…FX and other SSRIs increase extracellular serotonin (5-HT) levels acutely and serotonergic neurotransmission chronically, and these actions could underlie the reported adverse effects of these agents on pregnancy outcome and postnatal development (7,10,12). Serotonin plays a major role in the regulation of the HPA axis and adrenocortical secretion of cortisol (13).…”
mentioning
confidence: 99%